KORELASI KOMUNIKASI INTERPERSONA DALAM SOSIALISASI KONSUMSI JAMU SIAP SEDUH PADA EFEKTIVITAS PENANGANAN COVID-19 MASYARAKAT TLOGOSARI WETAN KECAMATAN PEDURUNGAN SEMARANG - Rekno Sulandjari (JURNAL ILMIAH EDUNOMIKA, 2021)
Public health is a very important factor and will determine the success of the local government in this case the Tlogosari Wetan village, because the community is the consumer of the service products produced. The measure of the success of service providers as needed and expected in this case is knowledge about Covid-19 and how to prevent and produce products that are expected to anticipate the widespread virus. The restoration of public health in Tlogosari Wetan Village was allegedly due to the use of ready-to-brewed herbs by opinion leaders in the village concerned. Thus, the role of opinion leaders in Tlogosari Wetan Village as a communication bridge is very necessary because the good services achieved will also have an impact on social scientific activities that can be carried out effectively with optimal positive impacts. Based on the results of research on the Correlation of Interpersonal Communication in Socializing the Consumption of ready-to-drink herbs carried out on the Effectiveness of Handling Covid-19, there are several conclusions, namely the results of the study indicate that Communication between Persons in Socializing the Consumption of Ready Seduh Jamu is in the high category. This is evidenced by the categorization of the research results by 62%. Meanwhile, the effectiveness of preventing and handling COVID-19 in the community in the Tlogosari Wetan sub-district also tends to be high, at 65%. This mostly begins with public anxiety about the number of victims due to Covid, so they have great respect for the socialization activities for consuming ready-to-drink herbs carried out by local opinion leaders. The final result of the cross tabulation is that there is a positive relationship between Interpersonal Communication in Socializing the Consumption of ready-to-drink herbs carried out on the Effectiveness of Handling Covid-19 in the community of Tlogosari Wetan Village. This is evidenced from the cross tabulation table which states that the categorization of the X variable is high, the Y variable is also high at 68%.